2021
DOI: 10.3390/nano11112977
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanomaterials Modified Biomimetic Dental Implants for Diabetic Patients

Abstract: Dental implants are used broadly in dental clinics as the most natural-looking restoration option for replacing missing or highly diseased teeth. However, dental implant failure is a crucial issue for diabetic patients in need of dentition restoration, particularly when a lack of osseointegration and immunoregulatory incompetency occur during the healing phase, resulting in infection and fibrous encapsulation. Bio-inspired or biomimetic materials, which can mimic the characteristics of natural elements, are be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 157 publications
0
6
0
Order By: Relevance
“…Their nanometer-size enhances their stability in the Utilizing polymers is a breeze, and the results may be endlessly varied molecular patterns that can be integrated into unique nanoparticle formations that have several potential medicinal applications. 41 Albumin, gelatin, chitosan and sodium alginate were the natural polymers used in the development of PNPs. 42 .…”
Section: Polymeric Nanoparticles and Its Drug Deliverymentioning
confidence: 99%
“…Their nanometer-size enhances their stability in the Utilizing polymers is a breeze, and the results may be endlessly varied molecular patterns that can be integrated into unique nanoparticle formations that have several potential medicinal applications. 41 Albumin, gelatin, chitosan and sodium alginate were the natural polymers used in the development of PNPs. 42 .…”
Section: Polymeric Nanoparticles and Its Drug Deliverymentioning
confidence: 99%
“…Tese materials have been recognized for exceptional mechanical, electrochemical, thermodynamic, optical, or chemical capabilities, as well as their distinctive structural dimensions [73]. Low toxicity and antiinfammatory have been reported when these carbon nanomaterials (CNMs) have been combined with diferent drugs, proteins, nucleic acids, and bioactive peptides [74]. Novel functionalized CNMs are characterized by biocompatibility, efective drug loading, and the absence of immunogenicity [75].…”
Section: Carbon-based Nmsmentioning
confidence: 99%
“…On carbon-coated zirconia, numerous in vitro studies showed superior cell adhesion compared to an uncoated disc. To the contrary of metals, plastics, and other ceramics, these carbonaceous materials do not experience fatigue [27,28]. However, because of their inherent fragility and poor tensile strength, they cannot be used in heavy load-bearing applications [4,16,25,27].…”
Section: Carbon-based Implantsmentioning
confidence: 99%